METODE MAUDU’Y DALAM PENAFSIRAN AL-QUR’AN (Meneguhkan Metode Penelitian Tafsir sebagai Metode Ilmiah) - Muhammad Zulkarnain Mubhar; Imam Zarkasyi Mubhar (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2021)
Understanding the Koran requires knowledge of methodology to make it easier to ground the purposes of divine revelation to humans. There are many methods of interpreting the Qur'an, but all of these methods have not been able to meet the needs and demands of the times, so we need a new method that is scientific in nature and can answer the challenges of the times and human problems. The methodological method that is in line with scientific research methods and does not contradict the objectives of the Qur'an and prophetic treatises is the maud} u> 'y method or thematic method, where this method can be used in all scientific disciplines to find answers. The Qur'an about it is comprehensive, comprehensive, and can be scientifically justified